1984
DOI: 10.1038/311019a0
|View full text |Cite
|
Sign up to set email alerts
|

Origins of biomolecular handedness

Abstract: Classical mechanisms proposed for the transition from racemic geochemistry to homochiral biochemistry in terrestrial evolution generally ascribe to chance the particular handed choice of the L-amino acids and the D-sugars by self-replicating systems. The parity-violating weak neutral current interaction gives rise to an energy difference between a chiral molecule and its mirror-image isomer, resulting in a small stabilization of the L-amino acids and the L-peptides in the alpha-helix and the beta-sheet conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
220
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(222 citation statements)
references
References 53 publications
1
220
1
Order By: Relevance
“…Theoretical studies revealed that very small, parityviolating weak neutral currents at the molecular level may distinguish mirror-imaged molecules and thus, be a basis for several amplification and detection mechanisms. [72][73][74][75][76] Recent literature cites claims of insignificantly small but still questionable differences seen between chiral isomers in their condensed states, like in supersaturated solutions, in crystals, in micellar aggregates, and on solid surfaces, etc. [77][78][79] Such a finding can have far-reaching implications, since, according to their propositions, these asymmetrical weak nuclear forces propagate to millions of other molecules via weak noncovalent interactions and land-up building asymmetrical population preferring a particular handedness.…”
Section: Homochiral Interaction In Hydrophobic Rod-like Polysilanes: mentioning
confidence: 99%
“…Theoretical studies revealed that very small, parityviolating weak neutral currents at the molecular level may distinguish mirror-imaged molecules and thus, be a basis for several amplification and detection mechanisms. [72][73][74][75][76] Recent literature cites claims of insignificantly small but still questionable differences seen between chiral isomers in their condensed states, like in supersaturated solutions, in crystals, in micellar aggregates, and on solid surfaces, etc. [77][78][79] Such a finding can have far-reaching implications, since, according to their propositions, these asymmetrical weak nuclear forces propagate to millions of other molecules via weak noncovalent interactions and land-up building asymmetrical population preferring a particular handedness.…”
Section: Homochiral Interaction In Hydrophobic Rod-like Polysilanes: mentioning
confidence: 99%
“…The favored mechanism by which amplification could occur, autocatalysis, was originally suggested by Frank [10], but has been elaborated since by others [11][12][13]. More significantly, it has been demonstrated experimentally [44][45][46][47], thus showing that autocatalysis does actually work.…”
Section: Resultsmentioning
confidence: 94%
“…This is comparable to or greater than that achieved in other models, although direct comparison is difficult. As with any model of chirality selection, amplification, presumably by autocatalysis [10][11][12][13], which has been demonstrated to occur in laboratory experiments [44][45][46][47], is required to produce the order-of-a-few percent magnitudes of the enantiomeric excess observed in the meteorites, and the homochirality observed on Earth. Additional details of the SNAAP model are discussed in [14] and [19].…”
Section: The Snaap Modelmentioning
confidence: 99%
“…What is not well understood, however, is the mechanism by which the initial imbalance is produced, and the means by which it always produces the left-handed chirality observed in the amino acids. This enigma has been discussed in numerous reviews in past years (see, e.g., [8][9][10][11][12][13][14]). …”
Section: Introductionmentioning
confidence: 99%